Analisis Permainan Tradisional Yang Telah Hilang Dari Peredaran Di Kampung AFD IV Sei Kebara - Taufiq Hidayah Tanjung, Nailan Nikmah Siregar (CV. PUSDIKRA MITRA JAYA, 2021)
This research shows traditional games that have been lost from circulation in AFD IV Sei Kebara Village. the method used is qualitative research. The result of the research is that traditional games are games that are cheap, easy, and provide a sense of joy and fun, besides that they can also improve children's intelligence and health. Parents should not forbid their children to play and do physical activities in the open, because this trains the immune system and anti-body pads in children so that children will avoid various kinds of diseases. From now on, it is hoped that parents and local residents can introduce traditional games to their children, so that traditional games which are characteristic of the nation's culture are not lost and can be preserved again.